2015
DOI: 10.1113/expphysiol.2014.081612
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle acid‐sensing ion channel 1: pathophysiological implication in hypoxic pulmonary hypertension

Abstract: What is the topic of this review? An increase in pulmonary arterial smooth muscle cell intracellular Ca(2+) levels facilitates the enhanced vasoconstrictor and vascular remodeling responses associated with hypoxic pulmonary hypertension. Identifying the mechanisms of altered Ca(2+) homeostasis will advance our understanding of the pathogenesis of pulmonary hypertension and identify potential therapeutic targets. What advances does it highlight? Acid sensing ion channel 1 (ASIC1), present in pulmonary arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 79 publications
(74 reference statements)
3
9
0
Order By: Relevance
“…ASICs are voltage-independent amiloride-sensitive and proton-gated cation channels, and their activity has been linked to a variety of physiological and pathological functions in the central and peripheral nervous system. The ASIC family of channel is constituted by five genes (ACN1–ACN5) encoding at least seven subunits (ASIC1a, -1b, -2a, -2b, -3, -4 and -5) [ 218 ]. The subunit composition of ASIC mainly determines the pH sensitivity and gating characteristics of the channel.…”
Section: Ion Channels In Pah Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…ASICs are voltage-independent amiloride-sensitive and proton-gated cation channels, and their activity has been linked to a variety of physiological and pathological functions in the central and peripheral nervous system. The ASIC family of channel is constituted by five genes (ACN1–ACN5) encoding at least seven subunits (ASIC1a, -1b, -2a, -2b, -3, -4 and -5) [ 218 ]. The subunit composition of ASIC mainly determines the pH sensitivity and gating characteristics of the channel.…”
Section: Ion Channels In Pah Pathophysiologymentioning
confidence: 99%
“…The subunit composition of ASIC mainly determines the pH sensitivity and gating characteristics of the channel. However, Acid sensing ion channel 1 (ASIC1) is expressed in a variety of tissues including PASMC, whose contribute to enhanced Ca 2+ entry mediating vasoconstriction, vascular remodeling, and right ventricular hypertrophy associated with hypoxic PH [ 218 , 219 ]. ASIC channels are mainly permeable to Na + but also conduct Ca 2+ [ 219 ].…”
Section: Ion Channels In Pah Pathophysiologymentioning
confidence: 99%
“…This model is consistent with the ability of different sub-types of Stim, TRPC, and Orai proteins to generate SOCE in pulmonary arteries ( Fernandez et al, 2012 ; Earley and Brayden, 2015 ; Wang et al, 2017 ). Moreover, other TRP channels such as transient receptor potential vanilloid-4 (TRPV4) and structurally unrelated Na + - and Ca 2+ -permeable cation channels such as acid-sensing ion channels-1 (ASIC1) may also contribute to SOC signaling in PASMC ( Goldenberg et al, 2015 ; Jernigan, 2015 ). Whether the mechanism linking store depletion and ASIC1 activation to generate SOCE is related with association of ASIC1 with Stim, Orai, TRPC proteins, or other unknown signal has not been elucidated.…”
Section: Store Operated Channels Receptor Operated Channels Structumentioning
confidence: 99%
“…[19][20][21] In addition, ASICs are also present in non-neuronal tissues such as testis, bone, dendritic cells, vascular smooth muscles, and endothelial cells. [22][23][24] Many reports have shown that ASICs play an important role in acidosis-associated physiological and pathological functions. 23,[25][26][27][28][29] Recent studies have shown that ASICs are expressed in glioma cells and mammary carcinoma and are involved in tumor pathogenesis.…”
Section: Introductionmentioning
confidence: 99%